Zapisz w postaci sumy algebraicznej i zredukuj wyrazy podobne.
a) 3a²(2a - b) - b(a³ - ab - 1) - 2ab ( - 1,5a + 3) =

b) a(b - c) + b(c - a) + c(a - b)=

c) - 4a²b(b - a/2 <ułamek>) + 2ab(2ab - a) =


Zad.13 str.35 . Książka pt. ' matematyka z plusem' zbiór zadań .


Z góry
Dziękuje :)

2

Odpowiedzi

2010-01-25T15:55:47+01:00
A) 3a²(2a - b) - b(a³ - ab - 1) - 2ab ( - 1,5a + 3) = 6a³-3a²b-a³b+ab²+b+2a²b-6ab=6a³-a²b-a³b+ab²+b-6ab
b) a(b - c) + b(c - a) + c(a - b)=ab-ac+bc-ab+ac-bc= 0
14 4 14
Najlepsza Odpowiedź!
2010-01-25T15:56:05+01:00
A) 3a²(2a - b) - b(a³ - ab - 1) - 2ab ( - 1,5a + 3) =
= 6a³-3a²b - ab³ + ab² + b + 3a²b - 6ab
=6a³-ab³+ab²+b-6ab

b) a(b - c) + b(c - a) + c(a - b)=
= ab - bc + bc - ac + ac - bc =
= ab - bc

c) - 4a²b(b - a/2 <ułamek>) + 2ab(2ab - a) =
= -4a²b² + 2a³b + 4a²b² - 2a²b =
= 2a³b - 2a²b
28 4 28